2003
DOI: 10.1002/jso.10217
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adjuvant chemotherapy in the long‐term outcome of patients with resected gastric cancer

Abstract: After curative surgery, adjuvant chemotherapy with mitomycin C, both alone or combined with Tegafur, improved the long-term cure rate over no postoperative chemotherapy in locally advanced gastric cancer patients. This benefit was not influenced by other prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
0
12
0
2
Order By: Relevance
“…Until recently, attempts at preventing recurrence, usually using adjuvant chemotherapy, have been ineffective, although Grau et al [2] presented a retrospective study demonstrating the improvement in the long-term cure rate of adjuvant chemotherapy over that of no postoperative chemotherapy. Macdonald [3] reported on the results of a large United States Intergroup study, which showed that combined chemoradiation, following gastric resection, improves the median time to relapse and overall survival, with adjuvant chemotherapy alone being of minimal benefit.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Until recently, attempts at preventing recurrence, usually using adjuvant chemotherapy, have been ineffective, although Grau et al [2] presented a retrospective study demonstrating the improvement in the long-term cure rate of adjuvant chemotherapy over that of no postoperative chemotherapy. Macdonald [3] reported on the results of a large United States Intergroup study, which showed that combined chemoradiation, following gastric resection, improves the median time to relapse and overall survival, with adjuvant chemotherapy alone being of minimal benefit.…”
Section: Discussionmentioning
confidence: 97%
“…Laparoscopic gastric surgical procedures have been found to be safe and feasible for early gastric cancer (EGC) and submucosal tumors [1]. On the other hand, adjuvant therapy, including chemotherapy alone or combined chemoradiation following gastric resection for advanced gastric cancer, has been reported to improve the median time to relapse and overall survival in selected patients [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Although perioperative chemotherapy [10] or adjuvant chemotherapy [15] alone (popular in Asia) have been shown to increase survival in addition to definitive surgery, adjuvant radiochemotherapy is still the common standard of care in the United States. Adjuvant radiochemotherapy is sometimes a more practical or better solution for patients with certain demography such as those who are operated by surgeons from community hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…24 Numerous randomized studies of adjuvant chemotherapy in gastric cancer have been performed, some of which have reported an overall survival benefit; 11,25 others have failed to show any such advantage. 13,26 There is no consensus on the role of adjuvant intraperitoneal chemotherapy because a consistent overall survival benefit has not been demonstrated in randomized trials. 3 The present retrospective study investigated the effect of adjuvant TAI chemotherapy and TACE on liver metastatic gastric adenocarcinoma, and showed that TAI chemotherapy was more effective in preventing liver metastasis than systemic chemotherapy.…”
Section: Discussionmentioning
confidence: 99%